L’impact touristique des nouveaux musées : analyse des relations entre l’environnement urbain et la spatialisation de l’impact à travers les exemples du Centre Pompidou-Metz et du Louvre-Lens - Mathias Boquet (Belgeo)
In the context of the recent increase of cultural flagship developments projects in the European cities engaged in economic conversion, this paper studies the tourist impact of these new museums on the territories of settlement. Through a comparative approach between the projects of cultural decentralization of the Centre Pompidou in Metz and the Louvre in Lens, the objective is to analyze the relation between the spatial context - that is urban environment at a local and regional scale - and the characterization of the impact. In particular, it is a question of showing what the conditions of a successful hybridization between the project of museum and its territory are.